2020
DOI: 10.1177/2309499020929166
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of postoperative swelling with a negative pressure treatment—A prospective study

Abstract: Purpose: Perioperative swelling and edema are the main factors that influence the time to definitive operative care, healing rate, as well as postoperative infection rate. Device-based negative pressure treatment is a new method to reduce post-traumatic and postoperative swelling of the upper extremities. The objective of this study was to evaluate a new negative pressure treatment with LymphaTouch® (Helsinki, Finland) to reduce perioperative swelling in upper extremity injuries. Methods: We analyzed 45 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Saul et al investigated the effect of negative pressure treatment on the upper extremity within a single-center prospective study in 45 patients. Consistent with our findings, they showed that negative pressure therapy could effectively reduce acute limb swelling after trauma and therefore decrease the time to surgery [ 17 ]. Though they investigated solely the application of negative pressure without having a control group, in context with findings from our study a significant impact of negative pressure treatment on limb swelling can be postulated.…”
Section: Discussionsupporting
confidence: 91%
“…Saul et al investigated the effect of negative pressure treatment on the upper extremity within a single-center prospective study in 45 patients. Consistent with our findings, they showed that negative pressure therapy could effectively reduce acute limb swelling after trauma and therefore decrease the time to surgery [ 17 ]. Though they investigated solely the application of negative pressure without having a control group, in context with findings from our study a significant impact of negative pressure treatment on limb swelling can be postulated.…”
Section: Discussionsupporting
confidence: 91%
“…In their results, they found that both methods led to a similar reduction in extremity circumference measurements, but the reduction in subjective pain sensation was more pronounced in the group receiving negative pressure therapy [48]. Similarly, Saul et al [25] found negative pressure therapy effective in reducing upper extremity swelling after surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Options outside of these methods, which are part of the Complex Decongestive Therapy group, include pneumatic compression, medical treatment, electrotherapy, and surgery [21,23]. Negative pressure massage therapy (NPMT) has started to be included in lymphedema treatment and its effectiveness has been investigated in recent years [24,25]. There are few studies in the literature that investigate the effectiveness of NPMT compared to manual massage therapy in lymphedema patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the only published peerreviewed prospective study that used an NPMT device to treat postoperative edema after orthopedic upper limb surgery. 26 That study reported no adverse effects and demonstrated a decrease in edema for 3 days after surgery. Based on our findings, NPMT has excellent potential as a conservative treatment for chronic breast cancer−related LE.…”
Section: Clinical Relevancementioning
confidence: 87%
“…In a prospective study that used a negative pressure device to reduce swelling after orthopedic upper limb surgery, 26 a decrease in arm circumference was found for 3 days after treatment. Evidence for the use of NPMT to treat LE is limited to conference abstracts and non−peer-reviewed manufacturer-initiated studies.…”
mentioning
confidence: 99%